EXISTENCE AND UNIQUENESS OF NASH EQUILIBRIUM IN A SUPPLY CHAIN NEWSVENDOR GAME - Chen, Y. J. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
This paper characterizes properties of Nash equilibriums for a supply chain newsvendor game with resource constraints. The newsvendor game has been modelled as a Stackelberg game in RN and also been reformulated as a fixed point problem for proving the existence and uniqueness.